2017
DOI: 10.1212/wnl.0000000000003955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a long-term intensive lifestyle intervention on prevalence of cognitive impairment

Abstract: Objective: To assess whether an average of 10 years of lifestyle intervention designed to reduce weight and increase physical activity lowers the prevalence of cognitive impairment among adults at increased risk due to type 2 diabetes and obesity or overweight.Methods: Central adjudication of mild cognitive impairment and probable dementia was based on standardized cognitive test battery scores administered to 3,802 individuals who had been randomly assigned, with equal probability, to either the lifestyle int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…These differences in populations, amount of weight loss achieved, and differences in exercise prescriptions across interventions are all possible reasons why findings from the current study may contrast with previous reports. However, our results were consistent with the Look AHEAD trial of over 3000 type 2 diabetics where a weight loss intervention was not shown to improve cognition . Weight loss or metformin may not be effective strategies to improve cognition for many breast cancer survivors.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These differences in populations, amount of weight loss achieved, and differences in exercise prescriptions across interventions are all possible reasons why findings from the current study may contrast with previous reports. However, our results were consistent with the Look AHEAD trial of over 3000 type 2 diabetics where a weight loss intervention was not shown to improve cognition . Weight loss or metformin may not be effective strategies to improve cognition for many breast cancer survivors.…”
Section: Discussionsupporting
confidence: 77%
“…33 where a weight loss intervention was not shown to improve cognition. 21 Weight loss or metformin may not be effective strategies to improve cognition for many breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ACCORD MIND sub-study, participants with long-duration T2D and high CV risk with intensive glucose, blood pressure, and lipid control did not have a reduction in cognitive decline over the 40-month follow-up period (54). Similarly, the Action for Health in Diabetes (Look AHEAD) research group reported that obese or overweight subjects with T2D assigned to a 10-year intensive lifestyle intervention (ILI) did not show better cognitive function compared with those assigned to diabetes support and education despite significantly greater weight loss in the ILI group (55). In Look AHEAD, cognitive function was not assessed at baseline prior to the intervention, and the absolute difference in weight at 10 years was small albeit statistically significant.…”
Section: Evidence Of Hyperglycaemia and Type 2 Diabetes As A Risk Facmentioning
confidence: 99%
“…2,3 In research contexts, evaluating participants' cognitive status is challenging because of the high cost of a comprehensive evaluation that includes neurocognitive testing, a clinical evaluation, interviewing knowledgeable family members, and optional ancillary laboratory tests or brain scans. 2,3 In research contexts, evaluating participants' cognitive status is challenging because of the high cost of a comprehensive evaluation that includes neurocognitive testing, a clinical evaluation, interviewing knowledgeable family members, and optional ancillary laboratory tests or brain scans.…”
Section: Introductionmentioning
confidence: 99%